(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Due to the small size, single-molecule device may be sensitive to the ambient molecules. Thus, it is significant for fabricating single-molecule sensors to understand the influence of ambient molecule on molecular device. Based on the ab initio calculations combined with non-equilibrium Green's function method, the adsorption effects of H_2O, CO_2 and NO_2 molecule on the pyrene-1,8-dithiol molecular junctions are studied systematically. The numerical results show that, the influence of H_2O or CO_2 molecule on the pyrene-1,8-dithiol molecular junction is very slight when they are adsorbed on the pyrene-1,8-dithiol molecules, which attributes to the closed-shell ground states of these two molecules. Different from H_2O and CO_2 molecule, being a radical, NO_2 molecule shows obvious influence on the electronic transport of pyrene-1,8-dithiol molecular junctions. The system with NO_2 adsorbate is more conductive in the positive and lower negative bias regime than those of the other two molecular systems, which is due to the evident coupling between the states of NO_2 molecule and pyrene-1,8-dithiol molecule.